Using Learning Media Based Autoplay Media Studio 8.0 on Student Learning Outcomes in Acid Base Material. (October 2020) - Irfandi,; Erna, Maria; Rasmiwetti,
Abstract: Purpose of the research to determine student learning outcomes by learning media based autoplay media studio 8.0 on acid-base material in class XI MIPA in SMAN 6 Pekanbaru. The research design used was posttest only group design with Mann-Whitney U nonparametric analysis that there were significant differences in student learning outcomes using learning media based on studio autoplay media 8.0 with the significance of Mann-Whitney U 0, 000 <0.005 with an average and observations of student attitudes during the learning process. The results showed learning outcomes of 89 compared to the control class 79. Based on observations of the learning process using the autoplay media studio 8.0 media, it was found that there was an increase in the attitude of cooperation, discipline, responsibility, activeness and curiosity of students. The results of this study are recommended to be applied to online learning.